2018
DOI: 10.1080/17461391.2018.1478449
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of the shot‐put: A method of assessing the mechanical work of the hand action force

Abstract: The aims of this study were to (1) propose a method for evaluating shot-putters mechanical power, (2) investigate the relationship between mechanical work of hand action force (W), peak power output (PPO) of different limbs and shot-put performance and (3) show which of these two parameters (W, PPO) were the most appropriate to characterize the explosive abilities of the shot-putter. Twelve junior right-handed shot-putters, practised glide technique shot-put throwers (personal best = 13.57  ±  1.72 m), partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…However, it is likely that the performance relied more importantly on the throwing technique and functional outcome as they are both directly related to velocity and angle of release. Shot-putting requires great explosive strength, together with the ability to perform precisely timed movements in a confined space (Landolsi et al, 2018). The athlete's objective is to project the shot as far as possible, but competition regulations restrict the technique that may be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is likely that the performance relied more importantly on the throwing technique and functional outcome as they are both directly related to velocity and angle of release. Shot-putting requires great explosive strength, together with the ability to perform precisely timed movements in a confined space (Landolsi et al, 2018). The athlete's objective is to project the shot as far as possible, but competition regulations restrict the technique that may be used.…”
Section: Discussionmentioning
confidence: 99%
“…Algeria achieved new Gold medals in the male competitions for elite throwers with impairment of cerebral palsy (Class F32/33). The level of competition was of high quality, where Performing well in shot-put consists of simply throwing the shot as far as possible (Landolsi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The athlete has control over four variables that directly influence the distance of the throw: release height, release angle, release dirction, and release velocity. 4,5 Previous studies have observed that release velocity is highly correlated with superior shot put performance, 5–9 and as the mathematical equation used to calculate throw distance is based on the quadratic equation, modifying the release velocity is theorized to have the greatest effect on the throw distance. 10 Other studies have suggested that neither release velocity nor other release parameters have any effect on throw distance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been done to understand the ideal ranges of each of these variables. Optimal release height has been shown to fall between 2.0 – 2.2 meters in elite athletes 7 and junior athletes, 6 although some studies have shown optimal performance with release heights in the range of 2.2-2.35 meters. 14 Obviously, athletes with larger statures (i.e., increased height or longer arm length) will be at an advantage in the shot put, as they will be granted a greater release height, increasing the amount of time the shot has in the air to travel horizontally.…”
Section: Introductionmentioning
confidence: 99%